2018
DOI: 10.4103/ijdr.ijdr_442_17
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of ghost cell odontogenic carcinoma: A case report with review of literature

Abstract: Ghost cell odontogenic carcinoma (GCOC) is a malignant odontogenic epithelial tumor which is an exceedingly rare, highly aggressive, rapidly growing, and infiltrative tumor forming the malignant counterpart of long-standing benign cystic lesions coming in the spectrum of calcifying odontogenic cysts. To date, only a few cases have been reported in the medical literature. A case of unusual presentation of GCOC is presented and the clinical, histopathological, and immunohistochemical features are discussed along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
1
10
1
Order By: Relevance
“…Mitoses are frequently observed. Immunohistochemical staining with a panel of antibodies demonstrated that neoplastic cells were strongly positive for cytokeratin and negative for vimentin, desmin, SMA, and CD34[43]. The expression of Ki-67 and MMP-9 may be associated with the proliferation, invasion, and prognosis of GCOC[33].…”
Section: Discussionmentioning
confidence: 99%
“…Mitoses are frequently observed. Immunohistochemical staining with a panel of antibodies demonstrated that neoplastic cells were strongly positive for cytokeratin and negative for vimentin, desmin, SMA, and CD34[43]. The expression of Ki-67 and MMP-9 may be associated with the proliferation, invasion, and prognosis of GCOC[33].…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be more common in Asian population with a male predilection (male:female ratio of 3.4:1). [ 4 47 ] The age of occurrence is variable from 10 to 89 but with a peak incidence in the fourth decade of life (mean age-43.4 years). GCOC occurs more frequently in the maxilla than the mandible with a usual presentation of a painful swelling with local paresthesias.…”
Section: Discussionmentioning
confidence: 99%
“…GCOC can appear as either “ de novo ” or as malignant transformation of a preexisting COC, CCOT, DGCT or other odontogenic tumors. [ 2 4 47 ] A careful patient history and clinical data is mandatory to ensure the origin of GCOC. In literature 28 cases found to be de novo in origin whereas 15 cases had previous history of ghost cell lesion spectrum COC, CCOT or DGCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations